Visualização experimental de escoamentos no interior de canais munidos de protuberâncias parietais - Bassan, Rodrigo Augusto [UNESP] (2011)
In the present work is accomplished a study of the flow within a channel with parietal 3 protuberances for Reynolds numbers less than 10 . The tests were conducted in a hydrodynamic tunnel vertical. Velocity profiles in the test section, as well as the turbulent intensity of the tunnel, vortex emissions were acquired through anemometry wire / hot film. Flow visualization techniques were employed as a tool for qualitative analysis, in the identification of flow patterns, as qualitative analytical tool to identify flow patterns; as a mechanism to support the implementation of experimental measurements, to assist in the correct positioning of airspeed probes; and finally as an additional tool of analysis, to facilitate interpretation of results. In every case the disposal was treated dimensional strictly. Another important factor of this work refers to the reconstruction of vertical hydrodynamic tunnel, which is located in the Flow View Laboratory, Department of Mechanical Engineering of UNESP - campus of Single Island; that with great commitment of Teachers Edson Vieira Del Rio, Sergio Said Mansur, lab technicians and a small contribution from me you can finish this project